Recent uses of carbon nanotubes & gold nanoparticles in electrochemistry with application in biosensing: A review - Alim, Samiul; Jaya Vejayan, Palliah; M. M., Yusoff; A. K. M., Kafi (Elsevier Ltd, 2018)
The innovation of nanoparticles assumes a critical part of encouraging and giving open doors and conceivable outcomes to the headway of new era devices utilized as a part of biosensing. The focused on the quick and legitimate detecting of specific biomolecules using functionalized gold nanoparticles (Au NPs), and carbon nanotubes (CNTs) has turned into a noteworthy research enthusiasm for the most recent decade. Sensors created with gold nanoparticles or carbon nanotubes or in some cases by utilizing both are relied upon to change the very establishments of detecting and distinguishing various analytes. In this review, we will examine the current utilization of functionalized AuNPs and CNTs with other synthetic mixes for the creation of biosensor prompting to the location of particular analytes with low discovery cutoff and quick reaction.